If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 1) + -8 = 5x + 2(-2 + x) Reorder the terms: 7(1 + x) + -8 = 5x + 2(-2 + x) (1 * 7 + x * 7) + -8 = 5x + 2(-2 + x) (7 + 7x) + -8 = 5x + 2(-2 + x) Reorder the terms: 7 + -8 + 7x = 5x + 2(-2 + x) Combine like terms: 7 + -8 = -1 -1 + 7x = 5x + 2(-2 + x) -1 + 7x = 5x + (-2 * 2 + x * 2) -1 + 7x = 5x + (-4 + 2x) Reorder the terms: -1 + 7x = -4 + 5x + 2x Combine like terms: 5x + 2x = 7x -1 + 7x = -4 + 7x Add '-7x' to each side of the equation. -1 + 7x + -7x = -4 + 7x + -7x Combine like terms: 7x + -7x = 0 -1 + 0 = -4 + 7x + -7x -1 = -4 + 7x + -7x Combine like terms: 7x + -7x = 0 -1 = -4 + 0 -1 = -4 Solving -1 = -4 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3/10x=6/5 | | .50x+.25(50)=44.5 | | 6+9x-3-18x= | | .19*54= | | g(x)=2xsquared-6 | | 4x^(5/4)-44=0 | | -6x/(x^2-6) | | 1/4x+1/9x+1/4x=37/18 | | (-2-3x)(-x)(-5x-45)=0 | | -3(9)(4)(-3)=x | | 1/4x-8+2/4x | | 12+9x=25+5 | | 1.5n-3x=6 | | -x-8+6x=-9+5x+1 | | 3(7g+12)=-48 | | 4(3x-4)=2(6x+1) | | 5.7x-3=4.7x | | 55-10x=15x | | (x/3-5)^2=16 | | -1=-18-5x | | 8+4y-2=8y+22-2y | | 5(x-10)+1=2(x-25)+x+1 | | 8n+17=5n+35 | | -2(x-3)=8 | | 9+2.7x=-4.8t-6 | | 8s+17s=225 | | 78+75+x/3=76 | | X-7/x+9=0 | | y/8=-8 | | y/8 | | -12x-3x=-5 | | 1/4=4z |